Formation of an Al‐Rich Niccolite‐Type Silica in Subducted Oceanic Crust: Implications for Water Transport to the Deep Lower Mantle. Issue 15 (13th August 2022) - Liu, Lu; Yuan, Hongsheng; Yao, Yao; Yang, Ziqiang; Gorelli, Federico Aiace; Giordano, Nico; He, Lixin; Ohtani, Eiji; Zhang, Li
Abstract: Subducted oceanic crust is enriched in free silica. Although being one of the silica polymorphs at lower‐mantle pressures, niccolite‐type phase (Nt‐phase) has not been documented in multicomponent metabasaltic or metasediment compositions relevant to subducting oceanic crust. Here, we report the formation of an Al‐rich Nt‐phase (∼24.4 to 32.4 wt% Al2 O3 ), coexisting with Al‐depleted bridgmanite (∼6.4 to 7.6 wt% Al2 O3 ), δ‐phase, and iron‐rich phase in model hydrated basalts over the pressure‐temperature range of 84–113 GPa and 1, 800–2, 200 K. Infrared spectroscopy of a pure synthetic Al‐rich Nt‐phase shows OH bending and stretching vibrations at high pressures, indicative of its hydrous nature. This study suggests that Al‐rich Nt‐phase can serve as a potential water carrier in subducted oceanic crust to the deep lower mantle. Plain Language Summary: Water is transported into Earth's interior via subduction of hydrated lithospheric plates. The water distribution in peridotitic and basaltic portion of subducted hydrated slabs is heterogeneous, which is dependent on the stability of water‐bearing minerals under the imposed pressure‐temperature and local mineralogical conditions. The aim of this study is to provide an understanding regarding the host for water transport within the subducted oceanic crust in the deep lower mantle. To this end, we performed high pressure‐temperature experiments on model hydrated basaltic rocks in a laser‐heated diamond anvil cell. Compared with the formation of CaCl2 ‐type silica in dry oceanic basalts from previous studies, a new water‐bearing Al‐rich niccolite‐type silica has been discovered in the present study. Our results imply that Al‐rich niccolite‐type silica can potentially carry water to the deep lower mantle in subducted oceanic crust. Key Points: Chemical reactions between water and a model basalt were investigated in laser‐heated diamond anvil cells under lower mantle conditions A new Al‐rich niccolite‐type silica containing ∼24.4 to 32.4 wt% Al2 O3 was identified, coexisting with Al‐depleted bridgmanite, δ‐phase, and iron‐rich phase Infrared spectroscopy showed that Al‐rich niccolite‐type silica contains structural water